Application of Health Belief Model (HBM) to Promote Preventive Behaviors Against Iron-deficiency Anemia Among Female Students of High School Fereydan City: A Quasi-Experimental Study - Hamed Mirzaei (آموزش بهداشت و ارتقاء سلامت ایران, 2017)
Background and objective: Iron deficiency is the most common nutritional problem in the world and is one of the main cause of anemia, especially in girls. The aim of this study was to evaluate the educational intervention program based on Health Belief Model (HBM) to increase preventive manners against iron-deficiency. Material and Methods: This quasi-experimental study was conducted on 128  female students of high schools in the second grade Friedan city in 2015. They were randomly divided into intervention and control groups. The data gathering tool was a questionnaire including demographic characteristics, HBM constructs and health performance questionnaires which were used after confirmation of validity and reliability of the tool. The data were analyzed using descriptive statistics, paired and independent t-test in SPSS 22 software. Results: Before training, there was not a significant difference in the mean scores of the health belief model constructs and health function between two groups, (p > 0.05). But three months after intervention, the mean scores of perceived susceptibility, severity, benefits, barriers, perceived self-efficacy, practice guidance and health performance were significantly different between two groups (p <0.001). Conclusion: Education based on HBM has been effective in promoting the preventive behaviors of iron deficiency anemia, therefore this model can be used as a framework for designing and performing education interventions to prevent iron deficiency anemia.